Dentin matrix degradation by host matrix metalloproteinases: inhibition and clinical perspectives toward regeneration - Chaussain, Catherine; Boukpessi, Tchilalo; Khaddam, Mayssam; tjaderhane, leo; George, Anne; Menashi, Suzanne (Frontiers in Physiology, 2013)
Bacterial enzymes have long been considered solely accountable for the degradation of the dentin matrix during the carious process. However, the emerging literature suggests that host-derived enzymes, and in particular the matrix metalloproteinases (MMPs) contained in dentin and saliva can play a major role in this process by their ability to degrade the dentin matrix from within. These findings are important since they open new therapeutic options for caries prevention and treatment. The possibility of using MMP inhibitors to interfere with dentin caries progression is discussed. Furthermore, the potential release of bioactive peptides by the enzymatic cleavage of dentin matrix proteins by MMPs during the carious process is discussed. These peptides, once identified, may constitute promising therapeutical tools for tooth and bone regeneration.